Characterization and therapeutic strategies for refractory vulvar lichen sclerosus: an 8-year single-center retrospective study and current evidence synthesis - Liu, Lin; Cui, Jun; Sun, Kailv; Yang, Min; Zhang, Qiuli; Yang, Kun; Jianmin, Chang (The Journal of dermatological treatment, 2025)
Untreated vulvar lichen sclerosus (VLS) can lead to irreversible anatomical changes and increase malignancy risk. Some patients show poor response to standard treatments, resulting in refractory cases (RVLS). To explore risk factors associated with RVLS and integrate treatment strategies for improved clinical management, we conducted a retrospective analysis, which included patients with VLS who visited our outpatient clinic between March 2017 and March 2025. Additionally, an evidence synthesis of the currently reported treatment regimens for RVLS was conducted. A total of 457 patients were included, of whom 36 were diagnosed with RVLS (7.9%). A multivariable logistic regression model identified comorbid autoimmune thyroid diseases (OR 2.45; 95%CI 1.09-5.34), perianal region involvement (OR 3.20; 95%CI 1.19-8.09), and presence of erosion/fissures (OR 3.13; 95%CI 1.44-7.29) as independent predictors for RVLS. Furthermore, the treatment approaches for 281 patients with RVLS across 20 studies included Janus kinase inhibitors (JAK), adalimumab, methotrexate, cyclosporine, photodynamic therapy (PDT), and laser therapy, with assessments of efficacy, side effects, and recurrence. Our study identified three predictive factors for RVLS, which may help in treatment decisions and reduce ineffective therapy. And therapies such as JAK and PDT show promise as optimized options, although larger studies are needed.